Konsep Pendekatan Gender Aware Counseling Berbasis Islam untuk Meminimalisir Aksi Radikalisme di Kalangan Perempuan Melalui Pemahaman Peran Gender - Nadhifatuz Zulfa (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
This article was written because of the radicalism that is taking place in Indonesia and involving women as one of the perpetrators. The role of women is now no longer a follower, supporter, or provocateurs in the act of radicalism in Indonesia, but even more extreme is the martyr